A socio-cultural analysis of smallholder borrowing and debt in southern Ethiopia. (January 2017) - Cochrane, Logan; Thornton, Alec
Abstract: This paper combines qualitative and quantitative research methods in an exploratory study of borrowing and debt in rural southern Ethiopia in order to understand the complexities of the rural finance system and frequency of borrowing and debt in rural, smallholder settings. By comparing geospatial location in relation to access to infrastructure, markets and services within a single agroecological setting, we explore the ways in which these factors influence the frequency of borrowing, sources, amounts and interest rates involved, as well as the duration and extent of borrowing and debt. We find great variation amongst the communities studied, highlighting the importance of the localized nature of borrowing and debt and identify barriers and opportunities that will support the (re)adjusting of policies and programs that would enable smallholder households to overcome cycles of borrowing and debt, and build assets. Highlights: Informal and formal borrowing is common in rural, southern Ethiopia; every surveyed household borrowed at least once in the last five years. The majority of loans were taken to meet basic needs (35%), followed by purchasing agricultural inputs (27%) and paying for healthcare costs (25%). Indebtedness is caused by vulnerability and necessity borrowing, with frequent instances of failures to make repayments. 49% of households failed to pay repayments on three or more occasions within the five-year period of study.